Education Program Review. State University System of Florida. Report and Recommendations - State Univ. System of Florida, Tallahassee; State Univ. System of Florida, Tallahassee ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
The Chancellor and the Board of Regents of the State University System (SUS) of Florida initiated a comprehensive review of Florida's colleges of education and related programs during 1984-85. The following concerns were addressed: (1) strengths and effectiveness of teacher education programs in the SUS; (2) the impact of teacher certification revisions on academic programs in education; and (3) how the SUS can best participate in the movement toward renewal of the public schools. This report focuses on the findings and recommendations of a panel formed to visit and assess each of the SUS's nine colleges of education. A brief description of the review process, including its schedules and procedures, is presented. Review panel findings and recommendations focused on: (1) the colleges of education; (2) college of education-public school relations; (3) revisions in teacher education programs; and (4) system level issues related to teacher education programs and teaching and schooling in Florida. Twenty-four specific recommendations regarding each of the nine colleges are presented. The review panel concluded that mechanisms and policies need to be established to assure statewide planning and coordinating of the efforts of SUS's nine colleges of education to act effectively with the public schools and community colleges. Appendices, making up half the document, include information of panel members, site visits, and teacher education programs. (CB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College School Cooperation; Educational Improvement; Elementary Secondary Education; Higher Education; Preservice Teacher Education; Program Evaluation; Public Schools; Schools of Education; State Colleges; Teacher Certification; Teacher Education Programs; Florida; Reports, Evaluative